Physiotherapeutic and technological approaches to lumbar disc herniation per sustainable development goal 3: Scoping Review - Ahmad, Danyal; Riaz, Saima; Kazmi, Syeda Khadija; Babur, Muhammad Naveed (Journal of the Pakistan Medical Association, 2026)
Objective: To map current physiotherapeutic and technological interventions for lumbar disc herniation, and to evaluate their alignment with Sustainable Development Goal-3. Method: The scoping review was conducted at Department of Allied Health The Superior University from January 2025 to June 2025 and comprised literature search on PubMed, Scopus, Physiotherapy Evidence Database, Cochrane Library, Directory of Open Access Journals, PakMediNet and Google Scholar databases for randomised controlled trials published between January 2015 and June 2025 about physiotherapeutic or technology-assisted interventions in lumbar disc herniation(LDH) patients which reported clinical outcomes. Data was extracted and subjected to narrative synthesis. Results: Of the 78 studies assessed, 15(19.2%) randomised controlled trials (RCTs) including 1,261 participants aged 18–80 years were analysed. Physiotherapeutic interventions(n=10) including manual therapy, spinal mobilisation, McKenzie and motor control exercises, Pilates and combination approaches, demonstrated consistent improvements in pain, disability, functional outcomes and quality of life. Adjunctive modalities, such as bamboo-based medicinal moxibustion, traction with paraffinotherapy, and neurodynamic mobilisation further improved functional outcomes or neuropathic symptoms. Technology-assisted interventions(n=5) including non-surgical spinal decompression, portable lumbar exoskeletons, digital app-based physiotherapy, Quick Response code-guided exercise programmes and high-intensity laser therapy, produced comparable improvements to conventional physiotherapy, with additional benefits in treatment adherence and patient satisfaction. Conclusion: Both conventional physiotherapy and selected technology-assisted interventions were associated with improvements in pain, disability and functional outcomes in lumbar disc herniation patients. Key Words: Lumbar disc herniation, Physical therapy modalities, Rehabilitation. Pain, Telemedicine.